2017
DOI: 10.1371/journal.pone.0166623
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Newborn Health in Karnataka State, India: The Community Level Interventions for Pre-Eclampsia (CLIP) Trial’s Baseline Study Results

Abstract: Existing vital health statistics registries in India have been unable to provide reliable estimates of maternal and newborn mortality and morbidity, and region-specific health estimates are essential to the planning and monitoring of health interventions. This study was designed to assess baseline rates as the precursor to a community-based cluster randomized control trial (cRCT)–Community Level Interventions for Pre-eclampsia (CLIP) Trial (NCT01911494; CTRI/2014/01/004352). The objective was to describe basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…In India, the stillbirth rates in different states reportedly range from 20 to 66/1000 births. Bellad et al reported a stillbirth rate of 28.6/1000 births from Karnataka where one of our Indian sites is situated [ 16 ]. The stillbirth rate for Maharashtra district where Nagpur is located as reported by the State Health Department is 17.8/1000 births.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the stillbirth rates in different states reportedly range from 20 to 66/1000 births. Bellad et al reported a stillbirth rate of 28.6/1000 births from Karnataka where one of our Indian sites is situated [ 16 ]. The stillbirth rate for Maharashtra district where Nagpur is located as reported by the State Health Department is 17.8/1000 births.…”
Section: Discussionmentioning
confidence: 99%
“…A 12-month mixed methods feasibility study preceded the internal pilot phase (1 February to 31 October 2014) in four clusters [7] , [8] , [9] , [13] , [14] , [15] , [16] . Progression to the definitive phase (additional eight clusters (1 November 2014 to 31 October 2016)) was based on the criterion of ≥50% acceptance of CLIP-indicated health facility referral.…”
Section: Methodsmentioning
confidence: 99%
“…The result of our study was in comparison to the study done by Bellad MB et al, and the UNICEF data which showed 69% and 66% of unbooked cases. 7,9 However, findings of the studies done by Puri A et al,…”
Section: Discussionmentioning
confidence: 99%
“…70.58% were from rural region (as per Table 3) which is in relation to the other studies done by Bellad MB et al, Urmila M et al, and Usharam et al, which were 69%, 76% and 75% respectively. [6][7][8] Maternal mortality is higher in rural population because of illiteracy, inadequate antenatal visits, inaccessible emergency health care services, lack of transportation facilities and late referral. Many patients are referred very late, in critical condition, unaccompanied by health care worker.…”
Section: Discussionmentioning
confidence: 99%